Pengaruh Nutrisi Organik Cair terhadap Pertumbuhan dan Produksi Bayam Merah (Althernanthera amoena Voss.) dengan Metode Hidroponik Wick System - Oshi Trisnalindo; Abdul Haris; Noor Aidawati (Universitas Lambung Mangkurat, 2020)
Red spinach is one type of extracted spinach that has a special characteristic that is red plants. Known as one of the highly nutritious vegetables because it contains a lot of protein, vitamin A, vitamin C and mineral salts that are needed by the body and contains anthocyanins that are useful in curing anemia. This study aims to determine the effect of the use of liquid organic nutrients from various organic materials on the growth of red spinach in the hydroponic cropping system. This research was carried out in the Win Hortinurs (Unlam 1) greenhouse using a single randomized complete design (CRD), namely by control treatment, P1, P2, P3, and P4. With control treatment using commercial AB Mix as much as 5 ml / L, the dose of liquid organic nutrition P1 is given at a dose of 20 ml / L, P2 as much as 25 ml / L, P3 as much as 30 ml / L, and P4 as much as 35 ml / L. Results research shows that liquid organic nutrition significantly affects the growth and development of red spinach plants. Furthermore, there are liquid organic nutrients, Pseudomonas fluorescens which have the ability to help plant development and reduce pH to near the standard pH value for hydroponics.